Alterações na expressão proteica de larvas de Aedes aegypti após intoxicação com o larvicida m-pentadecadienil-fenol isolado de sementes de Myracrodruon urundeuva - Souza, Terezinha Maria de (2013)
Currently, dengue fever is considered the most important arboviral disease in the world, emerging in countries where the disease seemed eradicated and reappearing in countries where before was under control. Despite all the efforts to produce and develop a vaccine against the disease, there is not a preventive therapy. Nowadays, the disease management is through the eradication of the mosquito vector Aedes aegypti. Despite the several options of synthetic insecticides available for management programs of vector populations, the emergence of resistant populations is presented as an obstacle in mosquito control vector. In addition to monitoring these resistant populations, it became evident that molecular studies may be the key to the sustainable management of these vectors. Thus, the present study aimed to evaluate the changes in protein expression of Ae. aegypti larvae treated with the organic larvicide m-pentadecadienil-phenol, a phenolic lipid isolated from Myracrodruon urundeuva seeds to elucidate the putative mechanisms of detoxification and molecular response to this compound. For this, two-dimensional electrophoresis (isoelectric focusing followed by electrophoresis in polyacrylamide gel under denaturing conditions - SDS-PAGE) of third-instar larvae treated with m-pentadecadienil-phenol, at sublethal concentrations (LC50 10.16 microg.mL-1) was performed. The results were compared to a non-treated group. Thirteen spots were identified as differentially expressed, and twelve were consistently identified in databases analysis of the spectra obtained by mass spectrometry (ESI-Q-ToF). After analysis of the pathways in which these proteins are involved, it was proposed that the larvicide m-pentadecadienil-phenol elicits the overexpression of proteins that promote the formation of more efficient barriers and that once inside the cells, it promotes oxidative stress which leads to increased lipid degradation metabolism, destabilization of lysosomal membrane, increased metabolism in response to stress due to the molecule’s toxicity and possibly results in programmed cell death (apoptosis).